A construção de mosaicos no plano por um aluno com transtorno do espectro autista - Flores, Gioconda Guadalupe Cristales (2018)
The present research had as objective to verify signs of significant learning in mosaics built in the plane, as a product of geometric transformations with regular polygons, by a student with Autism Spectrum Disorder (ASD). This disorder is characterized by behavioral symptoms of an individual that compromise socialization, communication and behavior constituting the triad of autistic symptoms, composing a spectrum from the milder level of symptoms to the most severe. The Theory of Significant Learning (TAS), which consists in relating previous knowledge and new knowledge, is the theoretical basis for this research. The presence and absence of previous knowledge of the student, about some geometric concepts necessary for the construction of mosaics, were detected from some activities planned for this purpose. Later, a didactic sequence was put into practice that was planned and applied in eight sessions, taking into account what was or was not detected as specific prior knowledge with the particularity of the research subject of being autistic. In the sessions were inserted previous necessary organizers and then material potentially significant as polygons made with concrete materials and manipulation of GeoGebra software. The analysis of the results shows that the adopted methodology favored the condition of the student and from what was observed during the didactic sequence there were signs of significant learning with the total and sometimes partial interaction of previous and new knowledge. This research also points to the inexpressive amount of research on TEA in Post-Graduate Programs in Education / Mathematics Education and considers it relevant to be able to contribute to the program that is linked and especially to Mathematics Education by pointing out a significant learning possibility of some contents by a student with ASD.